Pengaruh Kualitas Pelayanan Terhadap Tingkat Kepuasan Pasien Rawat Inap Rumah Sakit Santa Elisabeth Medan - Grace Putri Laia; Lea Sri Ita br P.A (Yayasan Literasi Sains Indonesia, 2022)
Patient satisfaction depends on the quality of services provided. Users of hospital services, in this case patients, demand quality services not only regarding healing from physical illness or improving their health status, but also regarding satisfaction with attitudes, always the availability of adequate facilities and infrastructure and a physical environment that can provide comfort. An accurate level of patient satisfaction is needed in an effort to improve the quality of health services. Therefore, measuring the level of patient satisfaction needs to be carried out regularly, regularly, accurately, and continuously. This study was conducted to analyze patient satisfaction and service quality based on the patient's interest in services and hospital performance assessment. The research used is a quantitative study with a cross sectional study design. And to determine satisfaction and service quality at Elisabeth Hospital Medan, we also conducted questionnaire questions to 1,000 respondents. treatment (35%) and as many as 400 respondents were not satisfied when they came to get services at the hospital (40%).